PENGARUH SENAM POCO-POCO TERHADAP KADAR TRIGLISERIDA DARAH - Rachmat, Chytra; Ticoalu, Shane H.R.; Wongkar, Djon (e-Biomedik, 2015)
Abstract: A common form of dyslipidemia is often associated with cardiovascular disease which is hypertriglyceridemia. Triglycerides in the body is mainly used as energy storage for a variety of metabolic processes. Poco-poco gymnastics from North Sulawesi. The purpose of this study is to find out the influence of poco-poco gymnastics to triglyceride blood levels. Methods: This study is experimental using one group pre and post test design, the subjects were 25 female students year 2013 Science and Mathematic Faculty of Pharmacyof Sam Ratulangi University Manado who met the inclusion criterias. Data was analyzed using paired t test. Results: Based on the research that has done from 25 subjects it was obtained that there was a decrease in mean triglyceride levels before and after poco-poco gymnastics for four weeks. However, this decrease was not significant (p=0,366). Conclusion: There was a decrease in triglyceride levels after poco-poco exercises for four weeks but this is not significant.Keywords : poco-poco gymnastics, triglycerideAbstrak: Bentuk umum dislipidemia yang sering dikaitkan dengan penyakit kardiovaskuler yaitu hipertrigliseridemia. Trigliserida dalam tubuh terutama dipakai untuk menyediakan energi berbagai proses metabolik. Salah satu faktor yang dapat mempengaruhi kadar trigliserida yaitu olahraga. Senam poco-poco merupakan senam yang berasal dari Sulawesi Utara. Penelitian ini bertujuan untuk mengetahui pengaruh senam poco-poco terhadap kadar trigliserida darah. Metode: Penelitian ini bersifat eksperimental dengan rancangan one group pre and post test dengan jumlah subjek penelitian 25 mahasiswi Program Studi Farmasi Fakultas MIPA Universitas Sam Ratulangi Manado yang memenuhi kriteria. Data dianalisis dengan uji t berpasangan. Hasil: Berdasarkan penelitian yang dilakukan pada 25 subjek penelitian diperoleh hasil yaitu terjadi penurunan rata-rata kadar trigliserida sebelum dan sesudah senam poco-poco selama empat minggu. Namun penurunan ini secara statistik tidak bermakna (p=0,366). Simpulan: Terjadi penurunan kadar trigliserida setelah latihan senam poco-poco selama empat minggu namun penurunan ini secara statistik tidak bermakna.Kata Kunci: senam poco-poco, trigliserida